Algebraic solution of the supersymmetric hydrogen atom in d dimensions - Kirchberg, A. (2003)
In this paper the N = 2 supersymmetric extension of the Schrodinger Hamiltonian with 1/r-potential in arbitrary space-dimensions is constructed. The supersymmetric hydrogen atom admits a conserved Laplace–Runge–Lenz vector which extends the rotational symmetry SO(d) to a hidden SO(d+1) symmetry. This symmetry of the system is used to determine the discrete eigenvalues with their degeneracies and the corresponding bound state wave functions.